Papillary Lesions of the Breast: What the Radiologist Should Know. (15th February 2018) - Gupta, Ekta; Dellacerra, Gary; Sheth, Monica
Abstract : Papillary lesions of the breast encompass a wide spectrum of benign and malignant lesions that arise from the ductal epithelium. These lesions comprise less than 10% of benign breast lesions, less than 2% of breast cancers, and less than 5% of all breast biopsies.1 It may be challenging to diagnose a papillary lesion as benign or malignant prospectively, given the considerable overlap in imaging features. Although imaging features may be similar, each pathologic entity has a unique biologic behavior. This CME activity reviews the common imaging features of papillary lesions of the breast, with emphasis on which imaging features can raise suspicion for atypia or malignancy. Techniques to optimize tissue sampling for accurate pathologic diagnosis also are addressed. Recognizing the variability of papillary lesions of the breast, their clinical features, imaging presentation, and pitfalls can facilitate appropriate diagnosis and guide treatment.